2019
DOI: 10.3389/fmicb.2019.01902
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Human Gut Microbiota Structure Caused by Quadruple Helicobacter pylori Eradication Therapy

Abstract: The human gut microbiome plays an important role both in health and disease. Use of antibiotics can alter gut microbiota composition, which can lead to various deleterious events. Here we report a whole genome sequencing metagenomic/genomic study of the intestinal microbiota changes caused by Helicobacter pylori (HP) eradication therapy. Using approaches for metagenomic data analysis we revealed a statistically significant decrease in alpha-diversity and relative abundance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 69 publications
(88 reference statements)
4
52
0
3
Order By: Relevance
“…We searched PubMed using the terms “Helicobacter”, “eradication” and “microbiota” for papers published from January 1, 2000, to March 12, 2020, in English. Sixteen studies using high‐throughput sequencing to assess alterations in the gut microbiota before and after H pylori eradication are summarized in Table 17‐32 . 10 publications focus on the impact of standard triple therapy and 5 studies address the long‐term (at least one year) effect after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We searched PubMed using the terms “Helicobacter”, “eradication” and “microbiota” for papers published from January 1, 2000, to March 12, 2020, in English. Sixteen studies using high‐throughput sequencing to assess alterations in the gut microbiota before and after H pylori eradication are summarized in Table 17‐32 . 10 publications focus on the impact of standard triple therapy and 5 studies address the long‐term (at least one year) effect after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other researchers recorded alpha diversity at weeks 0, 2, 8, and 48 reporting that the value was recovered at week 8 as well 53 . In accordance with these reports, most studies gathering follow‐up information within 2 months showed a decreased alpha diversity, whereas studies gaining information thereafter frequently reported no significant differences with baseline 9,50,51,53‐57 . Nevertheless, one study reported that both Sobs index and Chao index kept decreasing from week 0 to week 6 and week 26, though statistical significance was not reached 34 .…”
Section: Gastrointestinal Microbiota Reshaping Upon Eradication Therapymentioning
confidence: 53%
“…Another challenge for the antibiotic therapy of H. pylori are side effects. These may occur in some patients, the combination of two antibiotics causes more damage to the host gastrointestinal microbiota and leads to the imbalanced microbial population associated with the proliferation of gastrointestinal pathogens [56][57][58]. Additionally, PPI induction decreases in gastric acid secretion may increase the mobility of these pathogens, enable them to circulate in the gastrointestinal tract [59,60].…”
Section: Antibiotic Therapymentioning
confidence: 99%
“…H. pylori infection alters both the gastric and intestinal microflora [110]. At the same time, the bactericidal effect of antibiotic use and the pH change caused by PPI can lead to more severe disorders [56][57][58][59][60]. Clinical studies have confirmed that H. pylori infection reduces the diversity of the stomach microbiota in children and adults, and this microbiota may not be restored after eradicating the pathogen [15,111].…”
Section: Gastrointestinal Theorymentioning
confidence: 99%
See 1 more Smart Citation